Indigenous Cultural Heritage Tourism in Rompin, Pahang - Said, Haliza Mohd; Rahman, Salbiah Abd; Latif, Rohaizah Abd; Saidin, Munira; Aziz, Dahlia Abd (International Journal of Engineering and Technology, 2018)
The strategic purpose of this research project is to promote cultural heritage tourism for economic development among Jakun indigenous community in the district of Rompin, Pahang. This research is to determine whether tourism is a viable economic factor that could improve the living standards of the indigenous community through the use of culture and heritage. This research process is divided into four distinct phases, the first phase is the identification of resource analysis, the second phase is the summarization of the situational analysis, while the third phase is the identification of tourism products and activities, and the fourth and final phase is the recommendation of training programs for the area. A face-to-face interview is conducted with the Jakun people in six orang asli villages located in Rompin. The researchers have identified two potential Culture and Heritage areas located in Kampung Batu 3, Sabak and Kampung Selinkong.Â  Rumah Adat, indigenous homestay, nature trail and wood handicraft has been identified as tourism products from these areas. Training programs such as homestay operator, indigenous culture performance, nature guide and making wood handicraft can be proposed.